PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA (Survei Pada Perusahaan Manufaktur Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Pusparini, Anggi Aprila; Argamaya, Argamaya (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
The study aims to analyze how much the company size, leverage, probability, and managerial ownership can effect earning management. This research is used mining manufacture company that has been listed in the Indonesia Stock Exchange during 2013-2016 period of time as reasearch object. Variables used in this reasearch include company size, leverage, probability, and managerial ownership. The population used in this study is mining companies listed in Indonesia Stock Exchange since the year 2013 to 2016 respectively. The sample selection using purposive sampling method, with the acquisition of 36 samples in accordance with the criteria. Methods of data analysis used in this research is quantitative approach using multiple linear regression using Eviews 10 application. Secondary data was obtained from annual financial report of the mining company in the Indonesia Stock Exchange. Based on the reasearch result of mining company being observed sample, it comes to the conclusion that there is no effect of company size, probability, and managerial ownership percentage to the earning management. This result predicted that company size percentage, probability percentage, and managerial ownership can not affect earning management. As for leverage can eefect earning management. This result peredicted tha the presence of high leverage may cause a earning management act.